Early occurrence of temperate oak-dominated forest in the northern part of the Little Hungarian Plain, SW Slovakia. (December 2014) - Jamrichová, Eva; Potůčková, Anna; Horsák, Michal; Hajnalová, Mária; Barta, Peter; Tóth, Peter; Kuneš, Petr
Using a multi-proxy analysis of a postglacial sedimentary sequence from a lowland wetland, we address the possible drivers of change in the wetland habitats and surrounding landscapes of southwestern Slovakia. A 5 m-deep core in the Parížske močiare marshes was investigated for pollen, plant macro-remains, molluscs, organic content and magnetic susceptibility. The palaeoecological record extends from the Pleistocene–Holocene transition (≥11, 200 cal. BP) to the 5th millennium cal. BP and was correlated with a macrophysical climate model (MCM) and archaeological data. Our results show the transformation of an open parkland landscape with patches of coniferous forest to a temperate deciduous forest at the onset of the Holocene. The record is remarkable for an early occurrence of Quercus pollen and macro-remains around 11, 200 cal. BP and its early expansion (10, 390 cal. BP) in the vegetation. Such an early spread of Quercus has not previously been recorded in the region, where Corylus is usually the first to expand among temperate trees. This unusual development of forest communities was most probably triggered by a short-lived increase in precipitation and decrease in temperature, as reconstructed by the MCM model. Higher moisture availability and low temperature inhibited Corylus and favoured the spread of Quercus . Later, the climate became drier and warmer, which, together with fires, supported the expansion of Corylus . Since 7300 cal. BP, human activities became most likely the dominant influence on the landscape. Deforestation contributed to soil erosion, which halted the accumulation of organic material after 5520 cal. BP, followed by the accumulation of clay sediments.